WARIGA SEBAGAI MEDIA KOMONIKASI DALAM PENENTUAN DEWASA PADA UPACARA PERKAWINAN UMAT HINDU DI KOTA MATARAM - NI NYOMAN HARNIKA (GANEC SWARA, 2019)
This research is a descriptive study which aims to determine the existence of wariga as a medium of communication in the determination of dewasa at Hindu wedding ceremonies in the city of Mataram, and the communication process in determining dewasa at the Hindu wedding ceremony in the city of Mataram and the implications of using wariga as a communication medium in determining dewasa at the wedding ceremony of Hindus in the city of Mataram.     The results of the study show that the existence of wariga is still used as a guideline in the determination of dewasa by Hindus in the city of Mataram. The communication process in determining the adults at the wedding ceremony of Hindus in the city of Mataram by using wariga took place at the level of the Paruman Pandita PHDI Province of West Nusa Tenggara, and at the level of groups and individuals. The implications of wariga as a medium of communication at the wedding ceremony of Hindus in the city of Mataram are: 1) Increasing friendship between Hindus. 2) There is satisfaction and pleasure for Hindus who carry out wedding ceremonies. 3) The same understanding of pedagogies. 4) Increase the level of belief in Hindus towards the implementation of the Yajna. 5) Reducing differences of opinion about manhood in implementing the yajna. Breaking the wariga ban is bad for brides (brides) to get divorced, not have children or quarrel in the household.